A cognitive approach to lie detection: A meta‐analysis. (10th October 2015) - Vrij, Aldert; Fisher, Ronald P.; Blank, Hartmut
Abstract : Introduction: This article provides a meta‐analysis of a new, cognitive approach to (non‐)verbal lie detection. This cognitive lie detection approach consists of three techniques: (1) imposing cognitive load, (2) encouraging interviewees to say more, and (3) asking unexpected questions. Method: A meta‐analysis was carried out on studies using the cognitive approach, 14 of which directly compared the cognitive approach to a standard approach. Results: The cognitive lie detection approach produced superior accuracy results in truth detection (67%), lie detection (67%), and total detection (truth and lie detection combined, 71%) compared to a traditional standard approach (truth detection: 57%; lie detection: 47%; total detection: 56%). Conclusions: Practitioners may find it useful to use a cognitive lie detection approach in their daily practice.